Noninvasive Ventilatory Correction as an Adjunct to an Experimental Systemic Reperfusion Therapy in Acute Ischemic Stroke - Kristian Barlinn; Clotilde Balucani; Paola Palazzo; Limin Zhao; April Sisson; Andrei V. Alexandrov (Stroke Research and Treatment)
Background. Obstructive sleep apnea (OSA) is a common condition in patients with acute ischemic stroke and associated with early clinical deterioration and poor functional outcome. However, noninvasive ventilatory correction is hardly considered as a complementary treatment option during the treatment phase of acute ischemic stroke. Summary of Case. A 55-year-old woman with an acute middle cerebral artery (MCA) occlusion received intravenous tissue plasminogen activator (tPA) and enrolled into a thrombolytic research study. During tPA infusion, she became drowsy, developed apnea episodes, desaturated and neurologically deteriorated without recanalization, re-occlusion or intracerebral hemorrhage. Urgent noninvasive ventilatory correction with biphasic positive airway pressure (BiPAP) reversed neurological fluctuation. Her MCA completely recanalized 24 hours later. Conclusions. Noninvasive ventilatory correction should be considered more aggressively as a complementary treatment option in selected acute stroke patients. Early initiation of BiPAP can stabilize cerebral hemodynamics and may unmask the true potential of other therapies.